Ein-, to- eller fleirspråkleg ordbok? - Rauset, Margunn; Hannesdóttir, Anna Helga; Sigurðardóttir, Aldís (Nordiske Studier i Leksikografi, 2012)
This article explores possibilities and challenges that electronic media represent in a collection of three dictionaries with Icelandic as a source language and Danish, Norwegian and Swedish as target languages, i.e. the ISLEX dictionaries. This new medium allows dictionary users to conduct searches in many ways, both in lemmas and in equivalents. The dictionaries could therefore be considered as both bi-directional and multi-functional, but it is important to emphasize that they were not developed with this in mind. This article uses this as a point of reference to discuss whether ISLEX should be categorized as a mono-, bi- or multi-lingual dictionary.